Analisis Kebutuhan E-Modul Sejarah untuk Pembelajaran Sejarah Fase E di SMAN 01 Kec. Suliki - Febrian, Wahyuri; Ofianto, Ofianto (AHKAM, 2023)
This research aims to collect information on the needs for the development of E-Modules as a history learning medium at SMA 01 Kec. Suliki and analysis of the need for E-Modules as a medium for learning history in high school for Phase E (X E 3) class students. The research method used by researchers in this study is a qualitative descriptive method where the researcher is the key instrument and data processing is descriptive. Data collection techniques in this research used observation and interviews. The results of the discussion in this research are that students have low enthusiasm for learning history which is caused by the monotonous use of history learning media so that students need interesting and interactive learning media, for this reason the researcher offers to develop media that is interactive and can attract interest and motivation. and can help students in learning. The media that is the solution in this research is E-Module media which contains learning material content that is packaged digitally and is interactive. It is hoped that the e-Module can be a solution to problems related to students' low learning enthusiasm, so that effective history learning will be created and learning objectives can be achieved.